2006
DOI: 10.1038/sj.ijo.0803438
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, ghrelin, leptin and changes in body weight during a 1-year moderate-intensity physical activity intervention

Abstract: Objective: To investigate cross-sectional and longitudinal relationships among exercise, sleep, ghrelin and leptin. Methods: We randomly assigned 173 post-menopausal sedentary overweight (body mass index X24.0 kg/m 2 and 433% body fat) women aged 50-75 years living in western Washington State to either a facility-and home-based moderate-intensity physical activity intervention or a stretching control group. Fasting plasma ghrelin, leptin, measured height, weight and selfreported sleep were assessed at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 36 publications
(51 reference statements)
3
62
1
5
Order By: Relevance
“…Thus, ghrelin, which may act more rapidly on appetite, is associated with an acute, short-term measure of sleep while leptin, which is often considered to be a long-term energy balance factor, is associated with the more chronic long term sleep measure [32]. Another large study of post-menopausal women observed no association between self-reported sleep and measures of ghrelin or leptin [42]. The association between sleep and these hormones may be modified by age and gender.…”
Section: Laboratory Studies Of Sleep and Appetite Regulationmentioning
confidence: 98%
“…Thus, ghrelin, which may act more rapidly on appetite, is associated with an acute, short-term measure of sleep while leptin, which is often considered to be a long-term energy balance factor, is associated with the more chronic long term sleep measure [32]. Another large study of post-menopausal women observed no association between self-reported sleep and measures of ghrelin or leptin [42]. The association between sleep and these hormones may be modified by age and gender.…”
Section: Laboratory Studies Of Sleep and Appetite Regulationmentioning
confidence: 98%
“…There is rapidly accumulating evidence from both laboratory and epidemiological studies to indicate that chronic partial sleep loss may increase the risk of obesity and weight gain (Patel and Hu 2008;Zee and Turek 2006;LopezGarcia et al 2008;Rao et al 2009). The previous studies provided laboratory and clinical evidence indicating that sleep curtailment in young adults results in a constellation of metabolic and endocrine alterations, including decreased glucose tolerance, decreased insulin sensitivity, elevated sympathovagal balance, increased evening concentrations of cortisol, increased levels of ghrelin, decreased levels of leptin, and increased hunger and appetite (Patel and Hu 2008;Zee and Turek 2006;LopezGarcia et al 2008;Rao et al 2009;Spiegel et al 2004;Littman et al 2006;Gangwisch et al 2005;Erik Landhuis et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Tab. 1) bei Erwachsenen zum Zusammenhang zwischen Schlafdauer auf Übergewicht vor [46,47,48,50,51,52,53,54,55,56,57]. Davon wurden vier Studien nach Januar 2009 veröffentlicht.…”
Section: Erwachseneunclassified
“…Dabei war der niedrigste BMI in den meisten Fällen mit einer Schlafdauer von sieben bis acht Stunden assoziiert [46,51,55]. In wiederum anderen Studien zeigte sich überhaupt keine Assoziation zwischen Schlaf und Übergewicht oder Fettleibigkeit [46,47,50,52,54,55,57] [58]. Zudem wurde hier ein linearer Zusammenhang zwischen Schlafdauer und Gewichtsstatus gefunden (gepoolter Effektschätzer von −0,35 kg/m 2 BMI pro h Schlaf; 95%-KI: −0,57 bis −0,12; basierend auf sieben Studien).…”
Section: Erwachseneunclassified